2017
DOI: 10.1111/voxs.12387
|View full text |Cite
|
Sign up to set email alerts
|

Safe and sustainable plasmapheresis

Abstract: 471immunoglobulin levels and citrate-mediated alterations in calcium and bone metabolism), which also require regular monitoring and evaluation. Here, we provide details of our steps to maximize plasma collection volume and quality in Australia whilst monitoring and improving safety for our volunteer donors. Hospitalizations 2Á7( 1 Á8-4Á2) P < 0Á0001 VVR, vasovagal reactions; LOC, loss of consciousness; OR, odds ratio; 95%CI, 95% confidence interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Their data are consistent with that published by Pink et al [11] in Figure 1. These data demonstrated that for both males and females, the VVR rate was highest at the 13% TBV collection tier and progressively reduced as the TBV collection tier increased from 16% to 18%.…”
Section: Vvrs and Plasma Volume Collection Limitssupporting
confidence: 94%
See 1 more Smart Citation
“…Their data are consistent with that published by Pink et al [11] in Figure 1. These data demonstrated that for both males and females, the VVR rate was highest at the 13% TBV collection tier and progressively reduced as the TBV collection tier increased from 16% to 18%.…”
Section: Vvrs and Plasma Volume Collection Limitssupporting
confidence: 94%
“…An upper collection volume limit is required for both physiological and manufacturing reasons (i.e., blood bag limits). However, research [9,11,14] suggests that there are individuals who can tolerate higher collection volumes than others. Some donors develop symptoms before collection commencement because of anxiety or pain precipitating a VVR.…”
Section: Discussionmentioning
confidence: 99%